ANALISIS DAMPAK DAN STRATEGI PREVENTIF PERCERAIAN DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Gholib Assalam; Siti Rohimah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Divorce is a social issue with far-reaching impacts, not only on married couples but also on the psychological well-being of children and the resilience of the family as a whole. From the perspective of Islamic educational psychology, divorce is considered an obstacle to the family's educational function, which should serve as the primary foundation for the formation of an individual's personality, morals, and character. This paper aims to examine the impact of divorce from this perspective and to formulate preventive measures and solution-based approaches rooted in Islamic values. Emphasis is placed on the importance of premarital education, family counseling services, communication skills, and spiritual and emotional responsibility in creating healthy marital relationships. Furthermore, support from the immediate environment, such as parents, teachers, and the community, plays a crucial role in helping children overcome the psychological stress of divorce. Through an approach based on Islamic values ​​that is both anticipatory and curative, it is hoped that the family can continue to fulfill its strategic role as the primary and primary educational institution in fostering an emotionally and spiritually balanced generation.